Knowledge management - Khan, Altaf
Knowledge Management is a very personal activity that, if practiced widely, can improve organization's ability to achieve development results. Knowledge management mans talking responsibility what you know, who you know and what they know. Knowledge management begins and ends as a personal activity. Without the human understanding, personal context and need for immediate utility which we bring to bear on knowledge, all we have is raw data. Knowledge management tools ? including personal memory, data books, notebooks, file cabinets, email archives, calendars, post-it notes, bulletin boards, newsletters, journals, and restaurant napkins